Estimated returns and risks of oil prices Volatility in the international market for the period (1990 – 2017) - الجناني عمار نعيم; الجابري قصي عبود فرج (Journal of Petroleum Research and Studies, 2021)
The study aims at investigating the volatility of crude oil prices in the global market for the period (1990 - 2017). It also aims at estimating the returns of the global oil market and the risks that it faces as a result of volatility in the price of crude oil by using GARCH Models. The study revealed that the average return of volatility of Brent crude prices in the global market is about (1.12%) per month as well as the presence of a risk ratio in the global oil market of about (%0.32).